The Role of Support Group for Parents of Children with Special Needs - P.R Ujianti (Journal of Psychology and Instruction, 2018)
To have children with special needs is a challenge for parents. Acceptance on the children condition is the main key in determining attitudes and taking steps needed for optimizing the children’s growth and development. Unfortunately, many parents experience obstructions in accepting the condition of their children. This results in conflict within the parents themselves, with their spouses, or with other members of the family. This acceptance process itself has to go through several stages, namely denial, bargaining, anger, depression and acceptance. Many parents live in denial and anger before they can accept their children’s condition. Parents’ knowledge and understanding about their children’s special needs is one of the supporting factors which lead to acceptance. Yet the fact is, many parents especially from the middle and lower classes lack of information and believe more in superstitions in society. This fact surely hinders the steps needed to accept their children’s special condition and take proper care of them. The presence of support group which consist of parents of children with special needs and those concerned in the development of special needs children is a place for comfort, emotional release and information exchange for the parents.